Towards universalism? The obstructed process of healthcare reform in Bolivia - Sebastian Sirén (Institute for Advanced Development Studies (INESAD), 2011)
In this article a process-tracing approach is used to explore how different factors have contributed to the development of healthcare policy in Bolivia, in light of the current proposal to introduce a unified public healthcare system. The main findings are that although international relations and state bureaucrats have been crucial to the process of formulating policies, the introduction of comprehensive reform will depend on the ability of groups who currently lack access to the healthcare system to form progressive coalitions promoting universalism, as well as the ability of those who benefit from the current arrangements to maintain the status quo. The ability to introduce comprehensive reforms is thus connected to the ongoing processes of decentralisation and democratisation of political decision-making in Bolivia. Although state-corporative welfare state institutions have been shown to be difficult to transform, low coverage levels in such systems combined with a process of increasing political inclusion of previously marginalised groups poses serious challenges to the status quo as the social aspect of citizenship is brought up on the agenda. In order to achieve universal coverage of the healthcare system, however, basic social rights of all citizens must be institutionalised at the same time as the scope and quality of services must be secured in order to avoid segmentation and to encourage the financial participation of the formal and middle income sectors.
Keywords: 330; Bolivia; health care; social policy; institutional change; power resources; policy diffusion; Gesundheitsreform; Bolivien